Rencana Pengelolaan Limbah Cair Pabrik Kelapa Sawit (LCPKS) untuk Land Application - Istianto Budhi Rahardja; Sri Rejeki Ambarita (JURNAL CITRA WIDYA EDUKASI, 2017)
Liquid waste palm oil mill (LCPKS) is the result of the production of palm oil mill (POM) in the form of liquid besides CPO and PKO average often called to the by-product. LCPKS first be held in the pool waste prepared, and will be used to oversee the use of herbs of land application. Analysis performed on design pond waste, size pond actual that has been done, and data management LCPKS to land application. Research methodology uses the literature based on the results of the analysis that was done on waste treatment to land application generally in the POM, and data will processed using simple mathematic analysis. We do the comparison between design pond waste by needs a pond for manage LCPKS and needs LCPKS to land application. Based on the data obtained that planned a pond for processing LCPKS in POM 24,955.2 m3 capable of accommodate needs LCPKS to land application 163.8 m3 and needs the quantity of LCPKS that must be conducted for land application is 360 tons per day.